SARS-CoV-2 Delta variant: a systematic review of transmissibility and severity in children - Honeyman, Damian Alexander; Buisson, Elise; Hutchinson, Danielle; Kunasekaran, Mohana; Aagerup, Jannik; Chen, Xin; Moa, Aye; Hyde, Zoë (Global biosecurity, 2022)
Objectives: To review the evidence of the transmissibility and severity of infection with the Delta variant of SARS-CoV-2 in children.Design: Systematic review. Data sources: PubMed, Embase, medRxiv, Web of Science, and WHO COVID database.Study selection: English language original articles, case reports, commentaries, and letters with relevant primary data, which examined evidence for the transmissibility and severity of infection with the Delta variant of SARS-CoV-2 in children.Methods: Five databases were searched for articles from the period October 2020 to March 2022. Reference lists of eligible studies and grey literature were hand searched for additional studies for inclusion. Articles that provided adequate epidemiological data including infection, transmission, or severity (including hospitalisation and death) with probable or confirmed cases of the Delta variant of SARS-CoV-2 in children (aged ≤9 years) and adolescents (aged 10 to 19 years) were included. Data were extracted for country of origin; participant characteristics (age and sex); sample size; vaccination status; and outcomes, including incidence, secondary attack rate, hospitalisation, ICU, and mortality. All included studies were assessed for bias using the Joanna Briggs Institute Critical Appraisal checklists.Results: 298 studies were found through database searching. After screening, 21 studies were included in the systematic review. Of the included studies, all were deemed to be of moderate to high quality, therefore all were included in the final analysis. Increased incidence was reported in two population studies in the USA and Australia during the period of Delta predominance. Age-related data were available for 14 studies and showed higher rates of infection in older children compared to younger children. Attack rates in educational settings were higher when an adult was the primary case. Data on severity were available from 12 studies and showed that severe disease remained rare, with increasing hospitalisation numbers in proportion to increasing paediatric cases. Vaccination was protective for severe disease, with studies in the United States, Israel and Europe showing less healthcare encounters, emergency department presentations and hospitalisations amongst vaccinated adolescents. Several studies pointed to educational and household settings as key sites for paediatric infection with the Delta variant.Conclusion: A growing proportion of COVID-19 cases were diagnosed in children during the study period due to increased transmissibility of the SARS-CoV-2 Delta variant, with an increasing number of outbreaks observed in household and educational settings likely attributed to low vaccine coverage among children. While severe disease remains uncommon, the impact of vaccination in both adults and adolescents has been shown to reduce paediatric hospitalisation rates.